ANALYSIS AND CLASSIFICATION OF PERMANENT DENIAL-OF-SERVICE (PDOS) ATTACKS (Web of Technology: Multidimensional Research Journal, 2025)
In the constantly evolving field of cyber threats, Permanent Denial-of-Service (PDoS) attacks have emerged as one of the most destructive forms of cyber aggression. Unlike the well-known Denial-of-Service (DoS) attacks, which cause temporary service disruptions, PDoS attacks aim to inflict irreversible damage on systems, often requiring significant recovery efforts and even hardware replacement. To develop effective protective measures and bridge existing knowledge gaps, this study conducts an in-depth investigation of PDoS attacks, focusing on their distinctive features, implementation mechanisms, and potential future developments. Through a comprehensive analysis of real-world cases, various tactics and strategies used by attackers have been identified, including: Attacks on Internet of Things (IoT) devices, Manipulation of boot processes, Exploitation of embedded software vulnerabilities. As part of this research, a new classification of PDoS attack vectors is proposed, revealing the compromise mechanisms of targeted systems. The findings confirm the urgent need for the development of adaptive and resilient defense mechanisms capable of effectively countering PDoS threats in an increasingly interconnected digital environment.